The true costs of food production in Kenya - Benfica, Rui; Davis, Kristin E.; Oulu, Martin; Termote, Céline; Fadda, Carlo (International Food Policy Research Institute, 2024)
Key takeaways • True cost accounting allows for the measurement of hidden impacts of food production on the environment, human health, and society. • Our findings show that at the national level for all crop sectors: o Social costs account for 90% and environmental for 10% of external cost structure. o Major social cost sources are underpayment, child labor, and occupational health risks. o Major environmental cost sources are land-use expansion and climate change. • Findings at farm level in NATURE+ Initiative sites in Kajiado, Kisumu, and Vihiga, for the crop sector show that: o Direct costs (70% of true costs) are predominantly hired labor and seed costs o External costs represent about 30% of the true costs o Social externalities costs (84%) are greater than environmental costs (16%) o Forced labor is the most important impact, followed by child labor, underpayment, and gender wage gaps o Environmental externalities include land occupation (land use) and soil degradation